The historical archaeology of Marothodi : towards an understanding of space, identity and the organisation of production at an early 19th century Tlokwa capital in the Pilansberg region of South Africa - Anderson, Mark Steven (Department of Archaeology, 2014)
Includes bibliographical references (leaves 333-355).